Apparent digestibility coefficients of animal and plant feed ingredients for juvenile Pseudobagrus ussuriensis. (10th February 2017) - Che, J.; Su, B.; Tang, B.; Bu, X.; Li, J.; Lin, Y.; Yang, Y.; Ge, X.
Abstract: A study was conducted to determine apparent digestibility coefficients (ADCs) of dry matter (DM), crude protein (CP), lipid, gross energy, phosphorus and amino acids (AAs) from Peruvian fish meal (PFM), native fish meal (NFM), meat bone meal (MBM), dried daphnia meal (DDM), soybean meal (SBM), full‐fat soybean (FSBM), cottonseed meals (CSM), rapeseed meal (RSM) and corn gluten meal (CGM) for Pseudobagrus ussuriensis (7.8 ± 0.06 g). Test diets were formulated to contain a 70:30 mixture of reference diet to test ingredient with chromic oxide (5 g kg –1 ) serving as the inert marker. ADCs of DM ranged from 49.94% (CGM) to 87.11% (PFM), the highest ADCs of DM were observed in PFM and the lowest was found in CGM. ADCs of CP in the test ingredients ranged from 74.92% (CGM) to 93.41% (SBM). ADCs of crude lipid ranged from 51.80% (CGM) to 94.07% (PFM) for fish. ADCs of energy ranged from 56.42% (CGM) to 90.09% (PFM). ADCs of phosphorus ranged from 21.81% (CSM) to 65.70% (PFM). AA availability for the test ingredients followed a similar pattern to ADCs of CP, in which values for PFM, NFM and MBM were generally higher ( p  < .05) than those of other protein ingredients. Among all plant meals, the AA availability values in SBM were higher ( p  < .05) than those in CGM, CSM and RSM. The availability of most AAs in CGM was the lowest ( p  < .05) among all tested ingredients. In conclusion, PFM and NFM are good sources of available protein and AAs. When fishmeal supply is limited, MBM and DDM are substitutes for fishmeal reduction in P. ussuriensis diets; at the same time, SBM and FSBM are also very acceptable protein feedstuffs. However, CSM, RSM and CGM could not be used at high levels in P. ussuriensis diets because of their inferior digestibilities.